The Northwest Geysers EGS Demonstration Project, California: Part 1: Characterization and reservoir response to injection. (September 2016) - Garcia, Julio; Hartline, Craig; Walters, Mark; Wright, Melinda; Rutqvist, Jonny; Dobson, Patrick F.; Jeanne, Pierre
Highlights: A reservoir characterization of the Northwest Geysers EGS system is presented. We demonstrate that stimulation of a low permeability, high temperature reservoir can be achieved by injection of cold water. Data shows a favorable response to injection: increase in permeability, reservoir pressure and reduction of NCG. We identify the area stimulated as an independent reservoir volume of The Geysers geothermal field. The EGS experiment was not successful in mitigating the corrosive effects of Cl-bearing steam. Abstract: An Enhanced Geothermal System (EGS) Demonstration Project is currently underway in the Northwest Geysers. The project goal is to demonstrate the feasibility of stimulating a deep high-temperature reservoir (HTR) (up to 400 °C, 750 °F). Two previously abandoned wells, Prati State 31 (PS-31) and Prati 32 (P-32), were reopened and deepened to be used as an injection and production doublet to stimulate the HTR. The deepened portions of both wells have conductive temperature gradients of 10 °F/100 ft (182 °C/km), produce connate native fluids and magmatic gas, and the rocks were isotopically unexchanged by meteoric water. The ambient temperature meteoric water injected into these hot dry rocks has evidently created a permeability volume of several cubic kilometers as determined by seismic monitoring. Preliminary isotopic analyses of the injected and produced water indicate that 50–75% of the steam from the created EGS reservoir is injection-derived.